NOTES ON INDONESIAN FRESHWATER ALGAE II*Ichthyodontum, a new desmid genus from Sumatra. - SCOTT, ARTHUR M.; Prescott, Gerald W. (Research Center for Biology, 1956)
Described and figured are Ichthyodontum, a new genus belonging to the desmidiaceous algae, with I.sachlanii, a new species with its new variety parorthium, showing a peculiar bipolarity. From souther Sumatra.